Studi Deskriptif Tradisi Mencukur Alis pada Mempelai Wanita Persfektif Al-Qur’an Surah An-Nisa’ Ayat 119 dan Pemahaman Masyarakat di Kota Kisaran - Priwulan, Marpria; Darta, Ali (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The tradition of shaving the eyebrows of brides in Kota Kisaran is an entrenched cultural practice that is still practiced in the wedding procession. This phenomenon presents a dilemma between local cultural aesthetics and the guidance of Islamic teachings, especially the prohibition of changing Allah's creation as contained in QS. An-Nisa' verse 119. In the midst of growing religious awareness, there is a gap in understanding in the community regarding the law of shaving eyebrows in Islam. This study aims to analyze the meaning of QS. An-Nisa' verse 119 in the context of the tradition of shaving the bride's eyebrows and to describe the dynamics of the community's understanding of the practice. The method used is descriptive qualitative with theological-normative and ethnographic approaches, involving document analysis, in-depth interviews, and participatory observation. The results show that the practice of shaving eyebrows has a symbolic meaning in local culture, but also reaps differences of opinion in terms of sharia law. Some religious leaders consider the action as a form of changing God's creation which is forbidden, while the community interprets it as an aesthetic hearth. There have also been reconciliation efforts through persuasive da'wah approaches and alternatives to makeup without shaving. In conclusion, this practice reflects the ongoing dilemma between culture and religion, and shows the need for continuous education so that people's understanding becomes more contextualized and balanced.